Regulation of the Immune Response to α-Gal and Vector-borne Diseases - Cabezas-Cruz, Alejandro; Mateos-Hernández, Lourdes; Pérez-Cruz, Magdiel; Valdés, James J; Mera, Isabel G Fernández de; Villar, Margarita; de la Fuente, José (Trends in parasitology, 2015)
Vector-borne diseases (VBD) challenge our understanding of emerging diseases. Recently, arthropod vectors have been involved in emerging anaphylactic diseases. In particular, the immunoglobulin E (IgE) antibody response to the carbohydrate Galα1-3Galβ1-(3)4GlcNAc-R (α-gal) following a tick bite was associated with allergies to red meat, cetuximab, and gelatin. By contrast, an anti-α-gal IgM antibody response was shown to protect against mosquito-borne malaria. Herein, we highlight the interplay between the gut microbiota, vectors, transmitted pathogens, and the regulation of the immune response as a model to understand the protective or allergic effect of α-gal. Establishing the source of α-gal in arthropod vectors and the immune response to vector bites and transmitted pathogens will be essential for diagnosing, treating, and ultimately preventing these emerging anaphylactic and other vector-borne diseases.
Keywords: členovci - vektory; malaria; proteiny členovců; infekce přenášené vektorem; Humans; imunoglobulin E; Arthropod Vectors; alpha-gal; alergie; Th2 buňky; Host-Parasite Interactions; Hypersensitivity; lidé; zvířata; Arthropod Proteins; Disease Vectors; tick; Th2 Cells; vector-borne diseases; Animals; vaccine; interakce hostitele a parazita; Immunoglobulin E